KARAKTERISTIK PERMEN JELI BUAH PEDADA (Sonneratia caseolaris) BERDASARKAN VARIASI KONSENTRASI GELATIN - Azzahra, Putri; Moulina, Methatias Ayu; Widawati, Lina (LPPM UNIVERSITAS KAHURIPAN KEDIRI, 2025)
Pedada Fruit is a plant that grows in mangrove waters, is edible, has a unique aroma and sour taste. Pedada fruit can be processed into jelly candy. the aim of this research is to identify the effect of adding gelatin on the quality characteristics of pedada fruit jelly candy. The design of this study was a Completely Randomized Design (CRD) with 5 treatments, namely gelatin concentrations of 6%, 8%, 10%, 12%, 14%. Analysis was carried out yield, water content, vitamin C content, fiber content, protein content, ash content, organoleptics (color, taste, texture) and analysis of the benefits of pedada fruit jelly candy. Based on the results of calculations using a weighting test, the best treatment for pedada fruit jelly candy was with a gelatin concentration of 14%. Pedada fruit jelly candy with a gelatin concentration of 14% has a yield value of 48.03%, water content of 11.21%, vitamin C content of 0.01%, fiber content of 4.32%, protein content of 1.65%, ash content of 0.460%. color organoleptic 3.7 (like), taste organoleptic 4 (like), texture organoleptic 3.8 (like). From the analysis of profits obtained in one month of production, the best treated pedada fruit jelly candy provides a profit of Rp 1,409,000.00.